Plan de manejo de desechos sólidos del sector casco urbano de la ciudad de Zaruma, año 2018. - Romero Alvarado, Mayra Marisela (Machala : Universidad Técnica de Machala, 2018)
Municipal or urban waste is generated in the houses; Resulting from the elimination of the materials used by the inhabitants in their domestic activities, the waste that comes from any other activity within establishments or on the public thoroughfare that generates waste with home characteristics, and The resulting cleaning of the roads and public places. The majority of municipalities of Ecuador present a deficient management of solid wastes, at present the municipality of Zaruma has an area of environmental management that is in charge of the activities of sweeping, gathering, transport and disposition End, this area does not have adequate personnel for the management of solid wastes, therefore, does not have a plan of management of solid wastes, this problem affects to the environment and image of the sector urban center of the city, Since in some cases the citizens deposit in the sidewalks the garbage bags outside the time of collection being vulnerable to that the animals break them generating bad smells by the breakdown of the garbage and sometimes the machinery and equipment is scarce In order to develop a solid waste management plan, the importance of collecting data for the study of solid waste management was taken into account, since it allowed to know the reality of the health problem The methodology used to obtain data was considered in two stages: first stage for the evaluation of the current management of solid waste was through the tools of interview, survey and observation in situ; Second stage for the determination of the characteristics and composition of the solid waste generated In the sector was by sampling solid waste in several homes to obtain a heterogeneous sample and using methods of estimation direct as the method of quartering, equation generation per capita, equation of density and equation of percentage Component A current rate of generation per capita of 0.46 kg/hab/day, a density of 33.26 kg/m3 and a composition of 70.57% of organic waste and 29.43% of inorganic waste was obtained. Among the inorganics the plastic 6.88% and others as the waste of hygienic services 15.17% are the ones that the highest percentage reached. Considering that the proposal of the plan was designed for 10 years of useful life, the projection of population and GPC for the year 2028 in the sector urban center of Zaruma will have 11658 inhabitants, a GPC of 0.51 kg/hab/day, generating 5.92 ton/daily and 2159.36 ton/year. Through an SWOT analysis of the diagnosis of the current solid waste management, programs aimed at the community and the Municipal GAD were raised for each stage of solid waste management such as: environmental education, segregation and storage, exploitation, Collection and transport, and improvement of the landfill area, based on the methodology of the 4Rs (reduce, reuse, recycle and recover) and in current environmental regulations; Whose primary objective is that citizens have a responsible consumption to minimize the generation of solid wastes and classify them from their origin to provide a healthy and pleasant environment; And so have a better tourist development in the city heritage
Los desechos municipales o urbanos son los generados en las casas; que resultan de la eliminación de los materiales que utilizan los habitantes en sus actividades domésticas, los residuos que provienen de cualquier otra actividad dentro de establecimientos o en la vía pública que genere residuos con características domiciliarias, y los resultantes de la limpieza de las vías y lugares públicos. La mayoría de municipalidades del Ecuador presentan un deficiente manejo de los desechos sólidos, en la actualidad la municipalidad de Zaruma cuenta con un área de Gestión Ambiental que se encarga de las actividades de barrido, recolección, transporte y disposición final, dicha área no posee un personal adecuado para la gestión de desechos sólidos, por ende, no cuenta con un plan de manejo de desechos sólidos, dicho problema afecta al medio ambiente e imagen del sector casco urbano de la ciudad, ya que en algunos casos los ciudadanos depositan en las aceras las bosas de basura fuera del horario de recolección quedando vulnerables a que los animales las rompan generando malos olores por la descomposición de la basura y en ocasiones la maquinaria y equipo es escaso . Para elaborar un plan de manejo de desechos sólidos, se tomó en cuenta la importancia que tiene la recogida de datos para el estudio de la gestión de residuos sólidos, ya que permitió conocer la realidad del problema sanitario. La metodología utilizada para la obtención de datos se la consideró en dos etapas: primera etapa para la evaluación del actual manejo de los desechos sólidos fue mediante las herramientas de entrevista, encuesta y observación in situ; segunda etapa para la determinación de las características y composición de los desechos sólidos generados en el sector fue mediante la toma de muestreo de desechos sólidos en varias viviendas para obtener una muestra heterogénea y utilizando métodos de estimación directos como el método de cuarteo, ecuación generación per cápita, ecuación de densidad y ecuación de porcentaje componente; se obtuvo una tasa actual de generación per cápita de 0,46 kg/hab/día, una densidad de 33,26 kg/m3 y una composición de 70,57% de residuos orgánicos y 29,43% de residuos inorgánicos. Entre los inorgánicos el plástico 6,88% y otros como los residuos de servicios higiénicos 15,17% son los que mayor porcentaje alcanzaron. Considerando que la propuesta del plan se diseñó para 10 años de vida útil, la proyección de población y GPC para el año 2028 en el sector casco urbano de Zaruma tendrá 11658 habitantes, una GPC de 0,51 kg/hab/día, generando 5,92 ton/diarias y 2159,36 ton/año. Mediante un análisis FODA del diagnóstico del actual manejo de desechos sólidos se planteó programas dirigidos a la comunidad y al GAD Municipal para cada etapa de gestión de desechos sólidos como: educación ambiental, segregación y almacenamiento, aprovechamiento, recolección y transporte, y mejoramiento del área del relleno sanitario, basados en la metodología de las 4Rs (reducir, reutilizar, reciclar y recuperar) y en normas vigentes ambientales; cuyo objetivo primordial es que la ciudadanía tenga un consumo responsable para minimizar la generación de desechos sólidos y clasificarlos desde su origen para brindar un ambiente sano y agradable; y así tener un mejor desarrollo turístico en la Ciudad Patrimonio.
Keywords: DESECHOS; GENERACION; RECICLAJE; EDUCACION AMBIENTAL